Intention to accept Covid-19 vaccines and influencing factors among nursing students of Bagmati province, Nepal - Ghimire, Babita; Thapa, Namuna; Adhikari, Bhojraj; Prasad Upadhyay, Hari; Shrestha, Sushila; Sapkota, Sushma; Ghimire, Anita; Maharjan, Gayatri; Dhakal, Nisha; Kandel, Edina (Journal of Chitwan Medical College, 2026)
Introduction: The COVID-19 pandemic caused millions of infections and deaths globally. A safe and effective global vaccination coverage is crucial in controlling its spread. Cross-border movements and emerging variants remain significant threats. This study aimed to assess the intention to accept COVID-19 vaccines and the factors influencing it among nursing students in Bagmati Province, Nepal. Method: A cross-sectional analytical study was conducted among nursing college students in Bagmati Province, Nepal, from Dec 2021 to Dec 2022. Students were selected using a proportionate random sampling technique from 13 nursing colleges across nine districts. Data were collected using a semi-structured self-administered questionnaire comprising socio-demographics, COVID-19 exposure, and fear of COVID-19, knowledge, perceived barriers, and vaccination intention. Ethical approval was obtained from the Nepal Health Research Council (NHRC Ref.no. 1484). Data were analysed using SPSS version 20. Descriptive statistics were presented as n(%). The chi-square test and binary logistic regression were used to identify associations. A p<0.05 was considered significant. Result: Among 1,142 nursing students, 21 (2.8%) were unwilling to receive the COVID-19 vaccine. Good knowledge regarding COVID-19 was reported by 705 (61.7%). A statistically significant association was found between intention to receive COVID-19 vaccination and knowledge level (p<0.001) and perceived barriers to vaccination (p=0.028). Students’ fear of COVID-19 was significantly associated with ethnicity (p=0.004), family income (p=0.012), and academic year (p<0.001). Conclusion: Nursing students’ COVID-19 vaccination acceptance was associated with knowledge, perceived barriers, and fear of COVID-19. Targeted vaccination campaigns are needed to improve nursing students’ vaccine knowledge.